Model transformation chain to manage peripherals in mobile devices (2022)
The software industry nowadays is dealing with some problems like the fulfillment of quality attributes such as Portability, Interoperability, Maintenance, and documentation. That's why the OMG has proposed since 2000 the MDA as an interoperability specification to confront these problems. The present work attempts to show a description of the creation of a Model Transformation Chain (MTC) based on Model Driven Architecture (MDA) concepts applied in the context of software development on mobile devices. This MTC aims to generate automatically software to manage peripherals in this kind of device that runs on Android.